2010
DOI: 10.1021/pr100234w
|View full text |Cite
|
Sign up to set email alerts
|

Proteome, Phosphoproteome, and N-Glycoproteome Are Quantitatively Preserved in Formalin-Fixed Paraffin-Embedded Tissue and Analyzable by High-Resolution Mass Spectrometry

Abstract: Tissue samples in biobanks are typically formalin-fixed and paraffin-embedded (FFPE), in which form they are preserved for decades. It has only recently been shown that proteins in FFPE tissues can be identified by mass spectrometry-based proteomics but analysis of post-translational modifications is thought to be difficult or impossible. The filter aided sample preparation (FASP) method can analyze proteomic samples solubilized in high concentrations of SDS and we use this feature to develop a simple protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
203
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(214 citation statements)
references
References 42 publications
6
203
0
1
Order By: Relevance
“…Each sample set comprised of three biological replicates. Experimental controls from each sample set include wild-type tissues (comparison with knockout tissues) or cryopreserved tissues (comparison with FFPE tissues) or nonlabeled samples (comparison with 13 COD 2 formaldehyde-labeled samples). Three biological replicates were investigated in combination with a label-switch between 12 COH 2 formaldehyde and 13 COD 2 formaldehyde to provide statistical significance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample set comprised of three biological replicates. Experimental controls from each sample set include wild-type tissues (comparison with knockout tissues) or cryopreserved tissues (comparison with FFPE tissues) or nonlabeled samples (comparison with 13 COD 2 formaldehyde-labeled samples). Three biological replicates were investigated in combination with a label-switch between 12 COH 2 formaldehyde and 13 COD 2 formaldehyde to provide statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…However, a minor shift of the arginine to lysine ratio has been observed, indicating the persistence of yet undefined modifications or cross-links (8,11,12). Nevertheless, analysis of common posttranslational modifications such as phosphorylation and glycosylation showed equal preservations in FFPE and cryopreserved tissue specimens (13).…”
mentioning
confidence: 99%
“…The enzyme is not directly immobilized onto the ultrafiltration device, but the device acts as a "proteomic reactor" for detergent removal, buffer exchange, chemical modification and protein digestion, where trypsin is added in a dissolved form to the filter ( Figure 5). Lately four other papers have been published based on this method, and it seems promising for both membrane proteins, brain phosphoproteins and the N-glycoproteins (Wisńiewski et al 2009;Ostasiewicz et al 2010;Wisńiewski et al 2010;Zielinska et al 2010). We, however, found that the filter device was not able to deplete all SDS, and this can lead to problems with the subsequent LC-MS analysis (Hustoft et al 2011).…”
Section: From Microspin Columns To Filter-aided Sample Preparationmentioning
confidence: 99%
“…To improve our understanding of proteome alterations under pathological conditions, methods have been developed to analyze formalin-fixed paraffin-embedded (FFPE) tissues specimens by MS analyses (Ostasiewicz et al 2010; for detailed technical information, see also Gustafsson et al 2015;Maes et al 2013). FFPE tissue specimens represent preserved clinical material that is a unique protein source for studying human disorders and for the identification of disease biomarkers.…”
Section: Quantitative Ms-based Proteomicsmentioning
confidence: 99%